State Sukuk Development Strategy in the New Normal Era - Amaliah, Ima; Aspiranti, Tasya; Riani, Westi (KnE Social Sciences, 2023)
In the new normal era, the government has made many adjustments, including the state budget posture. The wider budget deficit faced by the government has encouraged the government to further optimize the ability of funding from the domestic market. This policy is not only to minimize risks due to exchange rate fluctuations but also to further strengthen the internal strength and role of society in national development. This article aims to identify strategies carried out by the government to mitigate the impact of COVID-19. Analysis was done using literature studies from various data references and literature sources. From the results of the data study, it was identified that there were many strategies rolled out by the government to strengthen the domestic economy. For one of them, the government is increasingly intensively issuing state sukuk with a variety of series that can accommodate many interests of individual investors. In addition, the published series of state sukuk are more based on accommodating environmental, social, and energy issues. Keywords: new normal, state Sukuk, state budge